An empirical analysis of the determinants of banks’ default risk- UK commercial banks - Dangol, Saila (2018)
This study applies panel data analysis on the determinants of default risk in UK commercial banks from 2011 to 2016. Non-performing loan is employed to measure the default risk. We review six bank-specific variables and three macroeconomic variables in our model. The model uses quantitative data collected from the database of World Bank and Bankscope. From the empirical results, we find that most of the bank-specific and macroeconomic variables are liable on affecting the banks’ default risk. The result implies that four bank-specific variables i.e. bank size, management inefficiency, and total loans has positive significant and profitability has negatively significant relationship with default risk of UK banks. With regards to macroeconomic variables, GDP and inflation has positive and significant relationship with default risk of UK banks. However, regulatory capital, loan quality and unemployment have no affect on default risk. Lastly, the outcome of this study is significance to banking practices, policymaking and further studies.